KAFE SEBAGAI SENTRA DISKUSI PUBLIK ANAK MUDA KOTA SERANG (Studi Kasus Kafe Umakite dan Kafe Mang Jaseng) - Atria Desiyanti; Husnan Nurjuman; Atih Ardiansyah (Universitas Sultan Ageng Tirtayasa, 2023)
In Serang City, Cafe Umakite and Mang Jaseng became pioneers in forming a friendly cafe for discussion for everyone, especially youth. Seeing this unique phenomenon, the researchers tried to explore the role and how the public opinion formed in the two cafes. This study uses a descriptive qualitative approach. The method used is a case study, at Kafe Umakite and Kafe Mang Jaseng, with a constructivism research paradigm. Data collection techniques used are observation, in-depth interviews, library research, and documentation, with triangulation as a test of the validity of the data. The results show that Umakite and Mang Jaseng cafes are proof that a cafe can be more than just a place to hang out and drink coffee. Their role as facilitators or even initiators of discussions can provide a platform for community aspirations. The topics discussed in this research at Cafe Umakite are: 1) Creative economy, 2) Multimedia, 3) Social issues, 4) Politics, 5) Public policy, 6) Social Media, 7) Technology. While the topics discussed at the Mang Jaseng Cafe were: 1) Employment, 2) Organizational activities, 3) Daily problems, 4) Issues in social media, 5) Economic issues, 6) Technology, 7) Public policy . The formation of opinions in these cafes comes from open discussions about public issues that exist in society. However, this does not mean that the discussion can necessarily be said to have an effect on government policy. However, the thing that needs to be underlined is that the topics are real and felt by society, therefore shaped the public opinion. Keywords: Cafe, public discussion, public sphere, public space.